ANALISA PERHITUNGAN SUSUT TEKNIS DI PT. PLN (PERSERO) RAYON SINGKIL - Syukri, Syukri; Muliadi, Muliadi; Akbar, Ali (Elektrika, 2024)
ABSTRACTPT. PLN (Persero) Rayon Singkil is working hard to carry out activities to reduce energy losses in the distribution network. There are two types of energy losses in the distribution network, namely technical losses and non-technical losses. This study of technical losses in Singkil rayon is discussed by approaching distribution asset data and load conditions using the Microsoft Excel program so that all data can be processed. Calculation of JTM losses, transformer losses, JTR losses, SR and APP losses. So the results obtained in Singkil Rayon with 4 feeders, namely in January 2023 were 10.4% with a composition of technical losses of 7.7% and non-technical losses of 2.7%, in February 2023 distribution losses were 8.6% with a technical loss composition of 7.8% and non-technical loss of 0.8%. Based on the calculation results, it makes it easier for PT. PLN (Persero) Rayon Singkil in analyzing and evaluating efforts that can be made to reduce distribution losses so that they become more efficient.                                                                                                 Keywords: Distribution system, Electrical energy, Energy losses, Technical losses, Non-technical losses. ABSTRAKPT. PLN (Persero) Rayon Singkil sedang berupaya keras melaksanakan kegiatan-kegiatan dalam hal penekanan susut energi pada jaringan distribusi. Susut energi pada jaringan distribusi ada dua yaitu susut teknis dan susut non teknis. Kajian mengenai susut teknis pada rayon singkil ini dibahas dengan cara pendekatan data aset distribusi dan kondisi beban dengan menggunakan program Microsoft Excel sehingga semua data dapat diproses. Perhitungan susut JTM, sussut trafo, susut JTR, susut SR dan APP. Maka hasil yang didapatkan pada Rayon Singkil dengan 4 penyulang yaitu pada bulan Januari 2023 sebesar 10,4 % dengan komposisi susut teknis sebesar 7,7 % dan susut non teknis sebesar 2,7 %, pada bulan Februari 2023 susut distribusi sebesar 8,6 % dengan komposisi susut teknis sebesar 7,8 % dan susut non teknis sebesar 0,8 %. Berdasrkan hasil perhitungan memudahkan PT. PLN (Persero) Rayon Singkil dalam menganalisa dan mengevaluasi terhadap upaya yang dapat dilakukan untuk menurunkan susut distribusi sehingga menjadi lebih efisien.